AULDOUS HUXLEY AND HIS DYSTOPIAN NOVEL “THE BRAVE NEW WORLD” - Rayimova Shahina Shermat qizi; Khamitov Eldorbek Erkin O’g’li (TADQIQOTLAR.UZ, 2024)
ABSTRACT. This article will discuss a brief summary of the information learned about "Brave New World," Huxley presents a world where citizens are controlled from birth through genetic engineering, psychological manipulation, and the use of mood-altering drugs.